Split Chloramphenicol Acetyl-Transferase Assay Reveals Self-Ubiquitylation-Dependent Regulation of UBE3B. Issue 23 (19th November 2021) - Levin-Kravets, Olga; Kordonsky, Alina; Shusterman, Anna; Biswas, Sagnik; Persaud, Avinash; Elias, Sivan; Langut, Yael; Florentin, Amir; Simpson-Lavy, Kobi J.; Yariv, Elon; Avishid, Reut; Sror, Mor; et al.
Graphical abstract: Highlights: A split-CAT reporter enables high density cell screening on chloramphenicol media. The assembly of split-CAT reports protein–protein and protein–ligand interaction. The split-CAT system harnessed to screen for potential drugs and molecular glues. The system enabled the discovery of self-ubiquitylation dependent UBE3B regulation. Abstract: Split reporter protein-based genetic section systems are widely used to identify and characterize protein–protein interactions (PPI). The assembly of split markers that antagonize toxins, rather than required for synthesis of missing metabolites, facilitates the seeding of high density of cells and selective growth. Here we present a newly developed split chloramphenicol acetyltransferase (split-CAT) -based genetic selection system. The N terminus fragment of CAT is fused downstream of the protein of interest and the C terminus fragment is tethered upstream to its postulated partner. We demonstrate the system's advantages for the study of PPIs. Moreover, we show that co-expression of a functional ubiquitylation cascade where the target and ubiquitin are tethered to the split-CAT fragments results in ubiquitylation-dependent selective growth. Since proteins do not have to be purified from the bacteria and due to the high sensitivity of the split-CAT reporter, detection of challenging protein cascades and post-translation modifications is enabled. In addition, we demonstrate that the split-CAT system responds to small molecule inhibitors and molecular glues (GLUTACs). The absence of ubiquitylation-dependent degradation and deubiquitylation in E. coli significantly simplify the interpretation of the results. We harnessed the developed system to demonstrate that like NEDD4, UBE3B also undergoes self-ubiquitylation-dependent inactivation. We show that self-ubiquitylation of UBE3B on K665 induces oligomerization and inactivation in yeast and mammalian cells respectively. Finally, we showcase the advantages of split-CAT in the study of human diseases by demonstrating that mutations in UBE3B that cause Kaufman oculocerebrofacial syndrome exhibit clear E. coli growth phenotypes.